Impacts of ICT as Tools in Teaching Biology in Senior Secondary Schools (International Journal of Academic Studies in Science and Education, 2024)
Information and Communication Technology (ICT) has been pivotal in training across the world. Due to the abstractness of Biology in schools, it is essential to develop an effective strategy of ICT tools to improve student’s learning process. Similarly, biology helps people understand how organisms adapt to their environment and the importance of biodiversity in sustaining our planet's delicate balance. Therefore, this study investigates the impacts of ICT as instructional material in teaching and learning biology and its gender dimension in senior secondary school at Ado-Odo Ota local government area of Ogun State, Nigeria. The sample size for this research was 240 which consisted of 180 Biology students and 60 Biology teachers. The research questions were investigated with descriptive statistics; Frequency and percentage with the Statistical Package for Social Science (SPSS). The results show a sizable correlation between information communication and technology and the performance of students offering biology in senior secondary school at Ado Odo Ota local government area of Ogun State. It also showed a notable difference in the performance of male students taught with information and communication technology-related facilities and female students taught with ICT-related facilities in Ado-Odo Ota local government area of Ogun State. It was concluded that ICT tools in Biology class can make students more interested in learning Biology. Therefore, Biology concepts should be incorporated into ICT tools to make learning Biology worthwhile, seamless, and entertaining.
Keywords: Academic Performance; Information and Communication Technology; ict; Student’s Performance; Biology